Adolescents’ healthy lifestyle - Marques, Adilson (2020)
Objective: Using a wide and representative sample of adolescents from 37 countries, this study aimed to analyze how age changes adolescents’ healthy lifestyle. Methods: The study included 148,839 adolescents who participated in the Health Behavior in School-aged Children 2010 survey. A composite score of a healthy lifestyle was created using the combination of daily physical activity, daily fruit and vegetable consumption, <2 h daily on screen-based behaviors, abstinence from alcohol, and abstinence from tobacco products. Healthy lifestyle measures were based on self-report. Results: 4.7% of boys and 4.4% of girls aged 11 years, 3% of boys and 2% of girls aged 13 years, and 1.5% of boys and 0.8% of girls aged 15 scored perfectly on the healthy lifestyle score. As age increased, the prevalence of adolescents with a healthy lifestyle decreased. In 37 countries and regions, the prevalence of healthy behaviors decreased linearly between early adolescence and the age of 15 years. Conclusions: In general, adolescents do not have a healthy lifestyle. Results from this study highlight that there is still much work to be done in promoting healthy lifestyles and to raise awareness among adolescents of the potential risk to their health status.